Pwede An advocacy campaign for the empowerment of persons with disabilities - Cortina, Myra Denise G. (2013)
Persons with Disability (PWDs) are typically seen in the society as incapable individuals. According to the Philippine Coalition on the Rights of Persons with Disabilities, there are policies that do not recognize PWDs as legally competent: in several articles of the Civil Code, in the rules of court, and policies concerning guardianship, and the appropriation for programs and activities for PWDs. Aside from that, PWDs have remained largely invisible because of discrimination which makes it more difficult for them to go to school, to find work or to participate in local activities. An effect of this, according to the United Nations, is that 80-90% of PWDs of working age are unemployed. Hence, attitudes and discrimination is a big factor to degrading the self-esteem of PWDs and this also plant the seeds of self-doubt that make PWDs do less than they actually can. On the other hand, virtue ethics is a concept which relies heavily on the influence role models have on people. In this study, a survey was conducted which revealed the effectiveness of using models in changing the attitude of PWDs. Thus, the study made use of the concept of virtue ethics to create an advocacy campaign, utilizing accomplished and empowered PWDs as role models, to influence the thinking of people and inspire Filipinos with disability to believe in themselves and make use of their capabilities. The project intends to increase the self-esteem of PWDs and push them to do more which will gradually lead to an improvement of their status in the society.